Perception and Satisfaction with Midwife-Led Model of Care Among Women in Ibadan, Nigeria (2020)
Background: Women's preference for natural childbirth and woman-friendly care has made some to patronize unskilled care providers, especially where Midwife-led care is not available which is known to contribute to maternal mortality. Aims: To evaluate women's perception and satisfaction with midwife-led model of maternal health care in Ibadan. Methods: A descriptive cross-sectional design was used. Simple randomization was used to select 367 women and data was obtained using an interviewer- administered questionnaire. Data was analyzed using descriptive and inferential statistics. Results: The mean age was 28.9 ± 6years. Most, 94.3% had good perception of MLMC. The mean satisfaction score was 39.0±5.5 out of a maximum score of 54 and 274(74.7%) claimed they had good experiences with the midwives. The experiences perceived as very important were quality of the caregiver-patient relationship, continuity of care and patient's involvement in decision-making. There was a significant association between level of education and perception of MLMC (fisher's value = 0.010) but there was no significant association between perception and satisfaction (x2= 0.622; p=0.430). Conclusion: Respondents' perception and satisfaction with midwife-led care was good. Midwives need to function more in the management of low risk pregnancies at various levels of health care.